Peningkatan Keterampilan Berhitung Perkalian Siswa Sekolah Dasar Melalui Penggunaan Buku Saku Perkalian pada Kegiatan Bimbingan Belajar KKN di Desa Taman Bali - Ni Komang Ayu Yuliantari; Nurul Isnaini Fitriyana (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This community service activity aims to improve elementary school students' multiplication skills through the use of the Multiplication Pocket Book in a tutoring program. The activity was implemented using a descriptive qualitative approach and involved 10 elementary school students as mentoring targets. The community service program was conducted over four sessions, each lasting 1 hour and 30 minutes. Data collection techniques were conducted through observation, interviews, and documentation throughout the mentoring process. The results showed a gradual improvement in students' multiplication skills, from understanding basic concepts to mastery of the 1-10 multiplication table. Furthermore, the use of the Multiplication Pocket Book, equipped with a learning achievement initialing system, increased student motivation, self-confidence, and active participation during the tutoring program. Therefore, the Multiplication Pocket Book can be used as a simple and effective learning medium in community service activities to support the improvement of elementary school students' basic arithmetic skills.